A new report of the uncommon Atlantic ribbon halfbeak Euleptorhamphus velox Poey, 1868 (Beloniformes: Hemiramphidae) from Brazil, with range update of the specie in the Southwestern Atlantic - Negro, Thiago Dal; Vaske, Teodoro [UNESP]; Carvalho-Filho, Alfredo; Rotundo, Matheus Marcos (Instituto de Ecologia y Ciencias Ambientales (IECA), 2023)
An adult specimen of Euleptorhamphus velox (Hemiramphidae) was captured in March 2021 from southern Brazil (26ºS). This record altogether with vouchers deposited in museum collections (MZUSP and MCZ), extends the published known distribution area of the species in about 3700 km in the southwestern Atlantic
Novo registro do raro peixe agulha-voador Euleptorhamphus velox Poey, 1868 (Beloniformes: Hemiramphidae) para o Brasil, com atualização de ocorrência no Atlântico Sudoeste
Keywords: Argentine Zoogeographical Province; distribution expansion; pelagic marine fish